Manufacturing jobs: Implicationsfor income inequality - Natalija Novta; Evgenia Pugacheva (Luxembourg Income Study (LIS), 2018)
The declining share of manufacturing jobs in overall employment has been a concern for policymakers and the broader public alike. Part of this concern stems from the widely held belief that manufacturing offers a unique source of well-paid jobs for less-skilled workers, and that the loss of these jobs worsens overall inequality. We find that manufacturing offers somewhat higher wages for the high and low-skilled workers in advanced countries, while there is no difference for middle skilled workers. We also find that inequality within services and industry, which includes manufacturing, are similar. While the displacement of workers from manufacturing to services in advanced economies has coincided with a rise in labor income inequality, this increase was mainly driven by larger disparities in earnings within all sectors.
Keywords: 330